Efficacy and Safety of Postoperative Pain Relief by Parecoxib Injection after Laparoscopic Surgeries: A Systematic Review and Meta‐analysis of Randomized Controlled Trials - Huang, Jun‐ming; Lv, Zheng‐tao; Zhang, Ya‐nan; Jiang, Wen‐xiu; Li, Han‐ning; Nie, Ming‐bo (Pain practice, 2018)
Objective This study aims to evaluate the efficacy and safety of parecoxib injection in pain relief after laparoscopic surgeries. Methods A comprehensive literature search based on 4 online databases (PubMed, Embase, Cochrane Central Register of Controlled Trials, and Web of Science) was applied to retrieve all related randomized controlled trials (RCTs). Two independent reviewers screened each article for eligibility according to the predetermined inclusion criteria. The Cochrane Collaboration's tool was applied to evaluate the methodological quality of included studies. A standardized data collection sheet was designed to extract data from included studies. RevMan version 5.3 (The Cochrane Collaboration, Copenhagen, Denmark) was selected to perform meta‐analysis. Results A total of 1,060 participants who were scheduled for gynecological laparoscopic surgery or laparoscopic cholecystectomy (LC) were enrolled in 12 selected RCTs. The methodological qualities of the studies were evaluated as moderate to high. The combined data showed that perioperative parecoxib injection could significantly reduce the proportion of patients who required adjuvant pain relieve after laparoscopic surgeries. Significantly lower pain scores in the parecoxib groups were observed, which proved that preoperative or intraoperative injection of 40 mg parecoxib was more effective than placebo for immediate pain relief after LC. But preoperative injection of 40 mg parecoxib showed no improvement compared with placebo in the management of immediate pain following gynecological laparoscopic surgery. The occurrence of adverse events showed no differences between perioperative parecoxib administration and placebo control. Conclusion Perioperative parecoxib administration was effective in reducing the proportion of patients who required adjuvant pain relief after laparoscopic surgeries without significant adverse events compared with placebo. The effect of parecoxib injection on immediate pain relief remains in question. Future RCTs with larger sample sizes are encouraged.